Two Stages One Qubit Quantum Teleportation via An Arbitrary Entangled Two Qubits Quantum Channel - Taufiqi, Muhammad; Purwanto, Agus; Subagyo, Bintoro Anang; Rahmawati, Rafika (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2023)
In this work, we consider two stages one qubit quantum teleportation protocol via an arbitrary entangled two qubits state. In the first stage, Alice use XOR gate and computational basis measurement, while for the second stage, Alice use Hadamard gate and another computational basis measurement. Alice sent measurement result to Bob via one classical bit each. As the result, we show that this teleportation can has unit fidelity if the channel used has non-zero two terms and maximally entangled. Then the protocol is applicable if the channel is one of four Bell's state.